Abundance analysis of extremely metal-poor stars. Issue 1 (January 2016) - Hansen, T; Hansen, C J; Christlieb, N; Andersen, J
Abstract: The outer atmosphere of the first generations of low-mass (M < 0.8 M⊙ ) stars retain to a great extent the original chemical composition of the interstellar medium (ISM) at the time and place of their birth. The composition of this pristine gas represents the nucleosynthesis of the very first massive stars, that produced and ejected the first heavy elements into the early ISM. Thus a detailed abundance analysis of low-mass, metal-poor stars can help us track these gasses and provide insight into the formation processes that took place in the very early stages of our Galaxy. Preliminary result of a 25-star homogeneously analysed sample of metal- poor candidates from the Hamburg/ESO survey is presented. The main focus is on the most metal-poor stars of the sample; stars with [Fe/H] < −4. The abundance pattern of these ultra metal-poor (UMP) stars is used to extract key information of the earliest ongoing formation processes (ranging from hydrostatic burning to neutron-capture processes).